2017
DOI: 10.1186/s13018-017-0636-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of supercapsular percutaneously assisted approach total hip versus conventional posterior approach for total hip arthroplasty: a prospective, randomized controlled trial

Abstract: BackgroundTotal hip arthroplasty (THA) has been one of the most successful orthopedic procedures over the past 30 years. Nowadays, the techniques of exposure for THA have undergone great changes, allowing surgeons to perform THA through mini-incisions. Recently, a novel minimally invasive surgical technique of the supercapsular percutaneously assisted total hip arthroplasty was reported in 2011. The purpose of this study was to compare the SuperPath approach with the conventional posterior approach, in terms e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
162
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(174 citation statements)
references
References 29 publications
5
162
7
Order By: Relevance
“…[67] A prospective study of 92 patients randomized to either SuperPATH or the posterior approach THA demonstrated a decreased rate of transfusions with SuperPATH, although the results were not statistically signi cant. [68] Allogenic blood transfusions have been associated with increased risk of infection after total joint arthroplasty, and the SuperPATH approach may help reduce this risk by reducing blood loss. [69] Rapid time to ambulation is a theoretical advantage of MIS THA approaches.…”
Section: Discussionmentioning
confidence: 99%
“…[67] A prospective study of 92 patients randomized to either SuperPATH or the posterior approach THA demonstrated a decreased rate of transfusions with SuperPATH, although the results were not statistically signi cant. [68] Allogenic blood transfusions have been associated with increased risk of infection after total joint arthroplasty, and the SuperPATH approach may help reduce this risk by reducing blood loss. [69] Rapid time to ambulation is a theoretical advantage of MIS THA approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Rachbauer and colleagues defined "a minimal invasive surgery" with the following characteristics: a short skin incision, preventing muscle splitting and/or detachment, and preserving the joint capsule [34]. Previous studies claimed that the SuperPath, approach as a true tissue-sparing minimally invasive approach, has less muscle damage mainly due to the preservation of external rotators [12,15,16,[35][36][37]. Our data discovered indeed a considerably shorter incision length in the SuperPath approach, however, and identified a noticeably longer operation time, more intraoperative blood loss, and comparable extents of soft tissue damage in the SuperPath approach compared with the PLA approach within the first 2 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperatively, all patients routinely underwent preadmission assessment, including radiograph of the pelvis and hip joint, blood tests, electrocardiogram, and anesthesiologist assessments. Inclusion criteria were as follows: (1) patients with body mass index (BMI) < 40 kg/m 2 ; (2) patients without serious functional deformity; (3) patients without the surgical history in affected side hip joint; (4) patients undergoing primary THA.…”
Section: Patientsmentioning
confidence: 99%
“…Total hip arthroplasty (THA) is an effective treatment for hip osteoarthritis and other disorders of femoral neck fracture, femoral head necrosis and acetabular dysplasia [1]. There are 3 main classical approaches to the hip for THA: posterolateral (Kocher-Langenbach), anterolateral (Watson-Jones) and anterior (Smith-Peterson).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation